Impact of Students’ Self-Assessment on Their Critical Thinking in Higher Education - Ahmad, Rukhsana; Rehman, Khalil Ur; Abdul Kadir, Zulida (Development in Language Studies, 2023)
The importance of critical thinking in students’ learning process is well established, however, few studies have evaluated the perceptions of university students regarding the correlation between self-assessment and critical thinking. This study measured the relationship between university students’ self-assessment and critical thinking. The researcher followed a quantitative research design to conduct this study. A total of 302 students participated in the study from the University of Swat, Khyber Pakhtunkhwa, Pakistan. The data from the sample group was measured through a self-developed questionnaire comprising 24 items covering different aspects of university students’ critical thinking and self-assessment. The collected data were analyzed using SPSS version 20 and the major findings of the study suggested that critical thinking helps students improve learning and cultivates the ability to make choices and guides them to understand problems and to contribute to identifying and solving problems. The study concluded that self-assessment also helps in taking responsibility and promoting understanding of course content